Association of Paracentral Acute Middle Maculopathy with Visual Prognosis in Retinal Artery Occlusion: A Retrospective Cohort Study. (21st May 2022) - Liang, Siying; Chen, Qingshan; Hu, Chenli; Chen, Miaohong
Abstract : Background . The association between paracentral acute middle maculopathy (PAMM) and visual acuity in patients with retinal artery occlusion (RAO) is unknown. This study explored the clinical features and prognostic factors for visual acuity of RAO accompanied by PAMM. Methods . This retrospective study included patients with RAO who underwent FFA and OCT examinations at Shenzhen Eye Hospital from July 2015 to June 2019. The changes in vision and macular structure were observed. Results . Eighty-eight patients were included. There were 58 patients (65.9%) with central RAO (CRAO) and 30 (34.1%) with branch RAO (BRAO). Fifty-two eyes were diagnosed with PAMM, of which 33 eyes (63.5%) were from CRAO patients and 19 (36.5%) were from BRAO patients. At diagnosis, the PAMM group had significantly better logMAR BCVA values than the no-PAMM group (median (IQR), 1.35 (0.725–2) vs. 2.15 (1.47–2.3), P = 0.002 ). In addition, the PAMM group had significantly better logMAR BCVA values during follow-up than the no-PAMM group (median (IQR), 1 (0.05–2) vs. 2 (1.15–2.3), P = 0.001 ). After adjustment for age, gender, CRAO/BRAO, comorbidities, and symptom duration, PAMM was associated with good visual acuity improvement (RR = 3.29, 95% CI: 1.29–8.37, P = 0.013 ). Conclusion . PAMM was associated with good visual acuity improvement during follow-up in patients with RAO.